Ways to Improve Job Training Policies for the Jobless - Heesuk Yun (Korea Development Institute (KDI), 2015)
In order to ensure that government policies do not produce government failure that impedes the vitality of the market and keeps disadvantaged individuals from becoming self-sufficient, the public assistance system needs to be reorganized, welfare programs that overlap different ministries should be linked, and appropriate performance indicators should be designated that do not distort the way public servants work. - Only 34 percent of individuals who participate in the Job Training Account Program for the jobless are hired, and 69 percent of those who are hired find jobs in industries that do not correspond to the area in which they received training. - Liberalizing prices when competition structure in price and quality has not been established runs the risk of wasting government funds and price increase without producing any meaningful benefits. - While the job training market needs to function properly in order to help the unemployed reenter the labor market, the government also has an important role to play in providing support for disadvantaged members of the society. As a result, the key is to achieve balance between the government and the market in the job training sector. - While the government initiated the development of job training in Korea, it is currently trying to allow the private sector and trainees to take the lead in the market. - Since government aid is directed to people who are not desperate to find work, the majority of trainees are flocking to areas that have a poor record for employment rate. - Excessive government aid is preventing the development of the training market by attracting trainees who are unconcerned with the quality of training and employment performance, which suppresses competition between training organizations and enables low-quality organizations to remain in business. - Under the current system, upperclass housewives who want to attend a training program as a hobby receive 50- 70 percent of the cost of the program along with cash allowance, while those in the middle and lower classes are provided with the majority of the cost of the program along with cash allowance. - The government is promoting price liberalization under the belief that low prices are causing the poor employment rate, but the cost of the training program is not as important as the question of who is responsible for covering the cost. - Under a support system in which beneficiaries have most of their training cost covered and also receive up to KRW400,000 in cash each month, there are structural limitations on determining who will receive assistance for job training using motivation to find work as a criterion. - A selective approach is required for government assistance, based on the understanding that the job training market should be designed for everyone searching for jobs and that people from vulnerable sectors need an appropriate amount of assistance in addition to such aid. - The fundamental cause for the surfeit of assistance for job training is lack of coordination in employment welfare programs administered by the Ministry of Employment and Labor and the Ministry of Health and Welfare. - The attempt to link employment and welfare in the original sense of the phrase must begin with new welfare programs.
Keywords: 330